2018
DOI: 10.1242/dev.163303
|View full text |Cite
|
Sign up to set email alerts
|

Glypican 4 and Mmp14 interact in regulating the migration of anterior endodermal cells by limiting extracellular matrix deposition

Abstract: During embryogenesis, the germ layers, including the endoderm, undergo convergence and extension movements to narrow and elongate the body plan. In zebrafish, the dorsal migration of endodermal cells during gastrulation is controlled by chemokine signaling, but little is known about how they migrate during segmentation. Here, we show that glypican 4 (Gpc4), a member of the heparin sulfate proteoglycan family, is required for efficient migration of anterior endodermal cells during early segmentation, regulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…Previously, we detected gpc4 transcript in the anterior endoderm (Hu, et al, 2018). Here, we found that gpc4 is also expressed in the posterior endoderm ( Fig.…”
Section: Embryossupporting
confidence: 75%
See 3 more Smart Citations
“…Previously, we detected gpc4 transcript in the anterior endoderm (Hu, et al, 2018). Here, we found that gpc4 is also expressed in the posterior endoderm ( Fig.…”
Section: Embryossupporting
confidence: 75%
“…S1D). GFP-Gpc4 is functional, as injection of the encoding RNA rescued C&E defects in gpc4 mutants (Hu, et al, 2018). Consistent with the expression pattern of sox17 (Alexander, et al, 1999), in this line GFP-Gpc4 signal was detected in the innermost tissue of the embryo, including in Kupffer's vesicle at the tailbud (TB) stage .…”
Section: Embryossupporting
confidence: 73%
See 2 more Smart Citations
“…Whole-mount RNA in situ hybridization (WISH) Digoxigenin-labeled antisense RNA probes for myl7 (cardiac myosin regulatory light chain) (Ye and Lin, 2013;Yelon et al, 1999), sox17 (sex determining region Y-box 17) (Alexander et al, 1999;Hu et al, 2018), southpaw (spaw) (Long et al, 2003;Panizzi et al, 2007) were synthesized by in vitro transcription. Staged embryos were fixed in 4% fish fix solution (4% paraformaldehyde, 4% sucrose, 0.1 M phosphate buffer pH 7.2, 0.12 mM CaCl2) at 4藲C overnight.…”
Section: Actin Polymerization Assaysmentioning
confidence: 99%